1985
DOI: 10.1295/polymj.17.73
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Thermally and Photochemically Initiated Cationic Polymerization

Abstract: Several new classes of triarylsulfonium salts have been discovered which possess enhanced efficiency as photoinitiators of cationic polymerization. One of these compounds was identified among the components of the Friedel Crafts reaction of benzene with sulfur monochloride and chlorine. Specific new syntheses were developed and are described for the synthesis of these compounds in high yields. The development of several new thermal initiator systems for cationic polymerization based on dialkyl-4-hydroxyphenyls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 8 publications
(2 reference statements)
1
29
0
Order By: Relevance
“…Most free-radical photopolymerizations cease within a millisecond or so after the irradiation is extinguished because of rapid termination. The classical living cationic photopolymerization of tetrahydrofuran can be carried out readily with diaryliodonium salt photoinitiators 49 ; however, the corresponding vinyl ether and epoxide polymerizations carried out at room temperature were not living and, not surprisingly, displayed considerable chain transfer. The photopolymerizations of these monomers do exhibit considerable "dark" reaction and can be classified as nonterminating.…”
Section: Photoinitiated Cationic Polymerizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most free-radical photopolymerizations cease within a millisecond or so after the irradiation is extinguished because of rapid termination. The classical living cationic photopolymerization of tetrahydrofuran can be carried out readily with diaryliodonium salt photoinitiators 49 ; however, the corresponding vinyl ether and epoxide polymerizations carried out at room temperature were not living and, not surprisingly, displayed considerable chain transfer. The photopolymerizations of these monomers do exhibit considerable "dark" reaction and can be classified as nonterminating.…”
Section: Photoinitiated Cationic Polymerizationsmentioning
confidence: 99%
“…76,77 Electron-beamcured coatings for packaging and high-performance aerospace composites are potential applications for this technology. The use of these salts as thermal 78 and redox 79 cationic initiators also has been reported. Very recently, we demonstrated that onium salt photoinitiators can be employed in efficient electroinitiated cationic polymerizations.…”
Section: Future Of Photoinitiated Cationic Polymerizationmentioning
confidence: 99%
“…The function of the noble metal catalyst in these reductions is not fully understood at this time. While it is well known that such catalysts complex with silanes bearing Si-H groups, [22,44] precisely how such complexes interact further with the onium salt to induce their reduction has not been elucidated at this time.…”
Section: S-aryl-ss-dialkylsulfonium Salts Ss-dialkyl-s-phenacylsulmentioning
confidence: 99%
“…Further, while benzoin smoothly reduces diaryliodonium salts with low reduction potentials (−5 kcal mol −1 ), [21] it is ineffective for the reduction of other types of onium salts. In particular, triarylsulfonium salts (−28 kcal mol −1 ), [22] for dialkylphenacylsulfonium salts (−14 k-cal mol −1 ) [23] as well as other types of sulfonium salts have reduction potentials that are considerably greater than diaryliodonium salts are not reduced by benzoin or its analogs. Consequently, we have sought alternative reducing agents that would potentially circumvent these drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…For evaluation of the lithographic potential, polycarbonates containing 10 wt% of a photochemical acid generator (PAG) (Cyracure = triarylsulfonium hexafluoroantimonate, or 2,6-dinitrobenzyltosylate) and 5 wt% thioxanthone were cast on a 100 itm polyester substrate (PET) as a 1 pm film. These PAGs are well known as light-sensitive proton sources in chemically amplified photo resists [16,17]. Thioxanthone was added as a sensibilizer since the absorption maxima (307 and 262 nm, respectively) of the PAGs were below the maximum emission of the UV source (maximum emission at 366 nm).…”
Section: Lithographic Behaviormentioning
confidence: 99%